A critical review of ultra-violet light emitting diodes as a one water disinfection technology - Kyle D. Rauch; Sean A. MacIsaac; Bailey Reid; Toni J. Mullin; Ariel J Atkinson; Anthony L Pimentel; Amina K. Stoddart; Karl G. Linden; Graham A. Gagnon (Water Research X)
UV light emitting diode (LED) disinfection technologies have advanced over the last decade and expanded the design space for applications in point of use, industrial, and now full-scale water treatment. This literature review examines the progression of UV LED technologies from 2007 to 2023 using key features such as total optical power, price, and wall-plug efficiency. The review found that optical power is increasing while the price per Watt is decreasing; however, the wall plug energy (WPE) is slowly improving over the last decade. These factors govern the feasibility of many UV LEDs applications and establish the current state of the art for these technologies. An analysis of inactivation rate constants for low-pressure, medium-pressure, and UV LED sources was undertaken and provides a comprehensive view of how current UV LED technologies compare to traditional technologies. This comparison found that UV LEDs perform comparably vs conventional UV technologies when disinfecting bacteria and viruses. Furthermore, comparison of reported reduction equivalent fluences for UV LED flow-through reactors at the bench-, pilot-, and full-scale were explored in this review, and it was found that LED treatment is becoming more effective at handling increased flowrates and has been proven to work at full-scale. UV LEDs do however require additional research into the impacts of water matrices at different wavelengths and the impact that each available LED wavelength has on disinfection. Overall, this work provides a broad assessment of UV disinfection technologies and serves as a state-of-the-art reference document for those who are interested in understanding this rapidly developing technology.